Case report of the one season change in swimming economy evaluated at high intensity domain, aerobic capacity and 200-m freestyle performance - Kim, J.; Muranaka, M.; Tanji, F.; Nabekura, Y.; Sengoku, Y. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Middle-distance swimming performance is predicted by swimming economy (SE) and various energetic parameters (Ribeiro et al., 1990; Costa et al., 2020). In swimming, Middle-distance swimming performance is predicted by swimming economy (SE) and various energetic parameters (Ribeiro et al., 1990; Costa et al., 2020). In swimming, VO2max is usually used as one of the most important physiological parameters to predict middle-distance swimming performance. However, VO2max values are similar among well-trained swimmers, as reported by Ribeiro et al. (1990). In contrast, SE is suggested to be a better predictor of swimming performance in well-trained swimmers compared to VO2max (Ribeiro et al., 1990). SE is defined as the amount of energy cost per unit of distance for given swimming velocity (Di Prampero et al., 1986), and is used as a parameter to evaluate swimming efficiency in previous research (Chatard et al., 1990). Most study on SE have reported assessing the aerobic energy demand by measuring steady-state oxygen uptake (VO2) at an intensity below the lactate threshold (LT), where most of the energy source is cover by aerobic metabolism. For instance, Kjendlie et al. (2004) assessed SE in children and adult swimmers at 1.0 m/s. There are two reasons for this. Firstly, assessing SE at intensities above the LT requires measuring the contribution of both aerobic and anaerobic energy metabolism by increasing the contribution of anaerobic metabolism. Secondly, VO2 above the LT intensity does not reach steady state and continue increasing until exhaustion, known as the slow component of VO2. Notably, middledistance swimmers generally perform above the LT intensity during their competitive events. Therefore, SE evaluated at high intensity domain may provide more informative results than SE evaluated at low intensity domain. However, despite various methods to assess SE at high intensity domain are reported (Termin & Pendergast, 2000), the relationship between swimming performance and SE evaluated at high intensity domain have not been investigated. Recent study reported that VO2 steady state is observed up to %40? (between LT and VO2max) during freestyle swimming in well-trained swimmers, and 200-m freestyle performance has a higher coefficient of determination with VO2max, LT and SE at an intensity above the LT compared to physiological parameters including SE at an intensity near the LT (R2 = 67% vs. 39%, respectively) (Kim et al., 2022). However, the relationship between change in physiological parameters and 200-m freestyle performance has not been investigated in welltrained swimmers. Thus, this study aimed to examine the relationship between one season changes in SE at high intensity domain, aerobic capacity, and 200-m freestyle performance in well-trained swimmers.O2max is usually used as one of the most important physiological parameters to predict middle-distance swimming performance. However, VO2max values are similar among well-trained swimmers, as reported by Ribeiro et al. (1990). In contrast, SE is suggested to be a better predictor of swimming performance in well-trained swimmers compared to VO2max (Ribeiro et al., 1990). SE is defined as the amount of energy cost per unit of distance for given swimming velocity (Di Prampero et al., 1986), and is used as a parameter to evaluate swimming efficiency in previous research (Chatard et al., 1990). Most study on SE have reported assessing the aerobic energy demand by measuring steady-state oxygen uptake (VO2) at an intensity below the lactate threshold (LT), where most of the energy source is cover by aerobic metabolism. For instance, Kjendlie et al. (2004) assessed SE in children and adult swimmers at 1.0 m/s. There are two reasons for this. Firstly, assessing SE at intensities above the LT requires measuring the contribution of both aerobic and anaerobic energy metabolism by increasing the contribution of anaerobic metabolism. Secondly, VO2 above the LT intensity does not reach steady state and continue increasing until exhaustion, known as the slow component of VO2. Notably, middledistance swimmers generally perform above the LT intensity during their competitive events. Therefore, SE evaluated at high intensity domain may provide more informative results than SE evaluated at low intensity domain. However, despite various methods to assess SE at high intensity domain are reported (Termin & Pendergast, 2000), the relationship between swimming performance and SE evaluated at high intensity domain have not been investigated. Recent study reported that VO2 steady state is observed up to %40? (between LT and VO2max) during freestyle swimming in well-trained swimmers, and 200-m freestyle performance has a higher coefficient of determination with VO2max, LT and SE at an intensity above the LT compared to physiological parameters including SE at an intensity near the LT (R2 = 67% vs. 39%, respectively) (Kim et al., 2022). However, the relationship between change in physiological parameters and 200-m freestyle performance has not been investigated in welltrained swimmers. Thus, this study aimed to examine the relationship between one season changes in SE at high intensity domain, aerobic capacity, and 200-m freestyle performance in well-trained swimmers.